Analisis Penerapan Prinsip Ekonomi Syariah dalam Pengelolaan Dana Nuris Medika (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study, entitled "Analysis of the Application of Sharia Economic Principles in Nuris Medika Fund Management," aims to analyze the extent to which Sharia economic principles are applied in the fund management system at the Nuris Medika healthcare institution. Sharia economic principles emphasize justice, transparency, mutual assistance (ta'awun), and the prohibition of riba (usury), gharar (gharar), and maysir (gambling). This study used a qualitative method with a descriptive approach. Data were collected through in-depth interviews, field observations, and documentation of managers and related parties at Nuris Medika. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The research results indicate that fund management at Nuris Medika largely adheres to Islamic economic principles, particularly in terms of transparency in fund use, social responsibility, and the implementation of an interest-free system in internal financial transactions. However, several aspects still need to be strengthened, such as the development of more systematic Sharia-based standard operating procedures (SOPs) and increasing Sharia economic literacy among all institution managers. Overall, the implementation of Islamic economic principles at Nuris Medika can be categorized as good and has the potential to become a model for financial management in Islamic boarding school-based healthcare institutions based on Islamic values.